Parent wellbeing and socioeconomic status during early childhood predicts 8 – 13 year old Indigenous children achieving Australian physical activity recommendations - Macniven, Rona; Stanley, Rebecca; Biles, Brett; Dumuid, Dorothy; Chandler, Paul; Olds, Tim; Okely, Anthony; Evans, John (My University, 2021)
Background: Physical activity is wholistically linked to culture and wellbeing among Aboriginal and Torres Strait Islander people (Indigenous peoples in Australia). Correlates of high physical activity among Indigenous children include living in a remote area and low screen time but little is known about determinants of physical activity. Purpose: To examine sociodemographic, parental social and emotional wellbeing (SEWB) and sedentary behavior determinants of physical activity among Indigenous children. Methods: The Longitudinal Study of Indigenous Children (LSIC) is the largest First Nations child cohort study in the world and collects data primarily through parental report. Multiple logistic regression analyses examined whether sociodemographic characteristics and parent SEWB, measured using the culturally relevant and validated Strong Souls Index (Strengths/resilience and Distress/anxiety/depression) at Wave 1 (age 0-5 years), predicted achieving physical activity guidelines of ≥1 hour/day moderate-vigorous physical activity (MVPA) at Wave 9 (aged 8 –13 years). Results: Achieving MVPA guidelines at Wave 9 was associated with the following Wave 1 determinants: high parent SEWB (Resilience; Odds Ratio (OR) 1.87 (1.32-2.65) but not Distress), living in remote (OR 3.66 (2.42-5.54)), low socioeconomic areas (OR 1.85 (1.08-3.17), main source of family income not wages/salaries (OR 0.66 (0.46-0.97)), and if families played electronic games (OR 0.72 (0.55-0.94)), after adjusting for covariates. Conclusions: Strategies to promote high parental wellbeing and resilience, and low levels of family screen time during the critical early years of life (0-5 years), even in families living in remote, low-SES areas with low employment, are important for Indigenous children’s future physical activity levels. Funding: The Longitudinal Study of Indigenous Children is funded and managed by the Australian Government.
Keywords: Adolescents and youth; Culture and language; Health and wellbeing; Lifestyle